Inherited Bleeding Disorders—Experience of a Not-for-Profit Organization in Pakistan. (November 2018) - Hussain, Shabneez; Baloch, Shahida; Parvin, Azra; Najmuddin, Akbar; Musheer, Farhana; Junaid, Mubashra; Memon, Rab Nawaz; Bhanbhro, Fareeda; Ullah, Hayat; Moiz, Bushra
Patient registry is a powerful tool for planning health care and setting groundwork for research. This survey reports a detailed registry of inherited bleeding disorders (IBD) and their management at a not-for-profit organization in a developing country to form the basis for planning development and research. We reviewed medical records of patients with IBD from 8 hemophilia treatment centers of Fatimid Foundation located in various cities. Information collected included sociodemographic data, diagnostic tests, severity of hemophilia A and B, number of bleeding episodes per year, site and frequency of hemarthrosis, and seropositivity for viral diseases. We analyzed 1497 patients from November 1, 2015, to April 30, 2016. There were 1296 (87%) males and 201 (13%) females with a mean age of 24.5 (11) years (range, 6 months to 65 years). Hemophilia A constituted the bulk of IBD (848, 57%) followed by von Willebrand disease (172, 11%), hemophilia B (144, 10%), platelet function defect (106, 7%), and rare bleeding disorders (70, 5%). Mucocutaneous bleeding (1144, 76%) and hemarthrosis (1035 patients, 69%) were the main complications. There were 1026 (69%) patients who received only blood components for treatment of any bleeding episode while the remaining 464 (31%) were on combination therapy (blood components and factor concentrate). Seroreactivity for hepatitis C was frequent (28%), while hepatitis B (1%) and human immunodeficiency virus (0.01%) were less commonly seen. This study was an important step toward a patient registry in a hemophilia treatment center in Pakistan. Hemophilia A is the most common bleeding disorder and hepatitis C is the most frequent treatment-related complication.